2018
DOI: 10.1002/cpch.34
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Self‐Replication for Evolution of a DNA Polymerase

Abstract: Compartmentalized self-replication (CSR) is an emulsion PCR-based method for the selection of DNA polymerases. E. coli host cells expressing a library of DNA polymerases are emulsified so that no more than a single cell is present in a single emulsion droplet. In a subsequent emulsion PCR step, the DNA polymerase protein, as well as the plasmid encoding it are released into the emulsion droplet and the genes that created the most active or abundant polymerase variants are exponentially amplified and can be pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We have previously demonstrated that isoprenoid analogues (Fig. 1) C15AlkOP and C15AlkOPP served as good substrates for metabolic labeling in COS-7 cells whereas C15AlkOH was incorporated with much lower efficiency[22]. In that study, we showed how labeling efficiency can be optimized by varying the probe concentration.…”
Section: Introductionmentioning
confidence: 79%
“…We have previously demonstrated that isoprenoid analogues (Fig. 1) C15AlkOP and C15AlkOPP served as good substrates for metabolic labeling in COS-7 cells whereas C15AlkOH was incorporated with much lower efficiency[22]. In that study, we showed how labeling efficiency can be optimized by varying the probe concentration.…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, several polymerase mutants were produced by adding site-directed mutagenesis into the exonuclease active site and C-terminal-conserved regions, which enhanced the incorporation of ribonucleotides and unnatural nucleotides (Blasco et al, 1992;Bonnin et al, 1999;Torres and Pinheiro, 2018). On the other hand, evolutionary methods are used for DNA polymerase engineering through the method of compartmentalized selfreplication (CSR) (Ghadessy et al, 2001;Ghadessy and Holliger, 2007;Abil and Ellington, 2018;Sakatani et al, 2019). For reaction conditions optimization, host DNA and environmental DNA may lead to false positive results in the amplification reaction, as phi29 DNA polymerase has high affinity for both single-strand and doublestranded DNA (Blanco et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A range of directed evolution strategies have been employed in the field. Compartmentalized self-replication (CSR) [ 139 141 ] challenges polymerases to PCR amplify their own gene inside an emulsion compartment. The exponential enrichment of highly active clones, as opposed to simple partitioning of active variants, makes CSR a powerful method.…”
Section: Templated Synthesis Of Non-natural Nucleic Acidsmentioning
confidence: 99%